Discursive-linguistic devices and strategies in spam e-mail narratives - Belli, Simone; Jiménez Bernal, Miriam (Círculo de Lingüística Aplicada a la Comunicación, 2020)
In this paper, we aim at relating emotions and gender stereotypes through the analysis of the narratives contained in spam e-mails. We will present four different types of spam e-mails from a corpus consisting of 450 emails, their length being between four and fifty-two lines of extension. They were received between late 2009 and mid-2016, and written in English, Spanish, Portuguese and French. Our analysis will be carried out in two steps. In the first step, the discursive-linguistic strategies will be described. In the second step, the linguistic expression of emotions will be addressed. We will rely on the Positioning Theory of Rom Harré to identify where authors and readers are positioned in the narratives.
Keywords: spam; linguistic-discursive analysis; deception; online anonymity; gender stereotypes